2006
DOI: 10.1128/aem.00013-06
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation-Independent Examination of Horizontal Transfer and Host Range of an IncP-1 Plasmid among Gram-Positive and Gram-Negative Bacteria Indigenous to the Barley Rhizosphere

Abstract: The host range and transfer frequency of an IncP-1 plasmid (pKJK10) among indigenous bacteria in the barley rhizosphere was investigated. A new flow cytometry-based cultivation-independent method for enumeration and sorting of transconjugants for subsequent 16S rRNA gene classification was used. Indigenous transconjugant rhizosphere bacteria were collected by fluorescence-activated cell sorting and identified by cloning and sequencing of 16S rRNA genes from the sorted cells. The host range of the pKJK10 plasmi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
78
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 99 publications
(86 citation statements)
references
References 42 publications
5
78
3
Order By: Relevance
“…Over 15 OTUs within the Actinobacteria phylum and more than 10 OTUs belonging to six different orders of Bacilli and Clostridia within the Firmicutes phylum were identified as transconjugants. Inter-Gram conjugal gene transfer has been shown with vectors consisting partly of the broad host range transfer machinery of RP4 recombined with the sacB gene from Gram-positive Bacillus subtilis (Schäfer et al, 1994), but has only exceptionally been identified in natural habitats (Musovic et al, 2006). Our observations suggest that it may be a more common process than previously considered.…”
Section: Resultscontrasting
confidence: 47%
See 1 more Smart Citation
“…Over 15 OTUs within the Actinobacteria phylum and more than 10 OTUs belonging to six different orders of Bacilli and Clostridia within the Firmicutes phylum were identified as transconjugants. Inter-Gram conjugal gene transfer has been shown with vectors consisting partly of the broad host range transfer machinery of RP4 recombined with the sacB gene from Gram-positive Bacillus subtilis (Schäfer et al, 1994), but has only exceptionally been identified in natural habitats (Musovic et al, 2006). Our observations suggest that it may be a more common process than previously considered.…”
Section: Resultscontrasting
confidence: 47%
“…This notion was supported when studying plasmid transfer to a range of strains isolated from marine water or wastewater treatment bioreactors (Sørensen, 1993;Inoue et al, 2005). With the use of fluorescent reporter genes to track plasmids, which reduces the need for selection and cultivation steps to identify transconjugants, it has become apparent that, in complex communities, broad host range plasmids can indeed be received by bacteria distantly related to the donor, even in the absence of selective pressure for plasmid carriage (De Gelder et al, 2005;Musovic et al, 2006Musovic et al, , 2014Shintani et al, 2014). However, these efforts, limited to inspection of a few hundred transconjugants at best, most likely underestimate the true diversity of transconjugal pools and do not accurately describe how plasmid permissiveness may vary across taxa in complex microbial communities.…”
Section: Introductionmentioning
confidence: 96%
“…Given the immense diversity of prokaryotes, the requirement for compatible cell contact would seem to be a greatly limiting step for HGT via conjugation. However, considerable evidence has accumulated over the years for conjugation between prokaryotes over large taxonomic distances (Musovic et al 2006). Some studies have even demonstrated trans-kingdom conjugation of plasmids from prokaryotes to eukaryotes.…”
Section: Mechanisms Of and Barriers To Horizontal Gene Transfermentioning
confidence: 99%
“…Hence, plasmid incompatibility can potentially restrict the access to part of the communal gene pool when similar plasmids are present. Plasmids such as the IncF, IncI, IncX or IncN group are, for example, rarely found outside the Enterobacteriaceae, and are therefore referred to as narrow host-range plasmids, while others, like the intensely studied IncP plasmids, are able to disseminate over a surprisingly wide variety of bacteria (Musovic et al 2006). Host range is therefore first and foremost determined by the plasmid replication mechanism, since a requisite of plasmid dissemination is an ability to replicate within every host through which it passes.…”
Section: The World Of Conjugative Plasmidsmentioning
confidence: 99%
“…IncP-1 plasmids synthesise two related replication proteins encoded by overlapping genes and are able to replicate and be stably maintained in all Gram-negative bacteria but not Gram-positive bacteria. However, recently a cultivation-independent examination of the host range of IncP-1 plasmid in the rhizosphere of barley revealed an extremely broad host range and detected the IncP-1 plasmid (pKJK10) in Arthrobacter sp., a member of the Actinobacteria (Musovic et al, 2006). Plasmids with a broad host range often appear to have lost restriction sites by point mutation and selection enzymes in the strain to which they are transferring.…”
Section: Conjugationmentioning
confidence: 99%